Assessment scales in depression and anxiety - Lam, Raymond W; Michalak, Erin E; Swinson, Richard P; Kennedy, Sidney H (Informa Healthcare, 2006)
The publication focuses on various scales used in the diagnosis of depression, mania and anxiety. Intended for professional public.
Keywords: Depressive Disorder; Bipolar Disorder; deprese; Anxiety Disorders; mánie; psychiatrie; bipolární porucha; Depression; depresivní poruchy; psychiatrické posuzovací škály; Mania; úzkost; Psychiatric Status Rating Scales; Anxiety; úzkostné poruchy